High linearity silicon carbide detectors for medical applications - Nurul Syazwina, M.; Horsfall, A.B (2016)
Silicon carbide is well known as a radiation hard semiconductor, that has been demonstrated in a range of detector structures for deployment in application where the ability to tolerate high radiation dose is imperative. This includes applications in space and nuclear environments, where the ability to detect highly energetic radiation is important. In contrast, medical treatment uses a range of radiation dose rates and energies and here we investigate the response and linearity of a highly radiation tolerant detector fabricated using silicon carbide to dose rates in the range of 0.185mGy.min−1. This dose rate is typical of those used for medical imaging purposes, rather than radiotherapy treatment. The data show that the generated current originates within the depletion region of the detector and that the response is linearly dependent on the volume of the space charge region. The realization of a vertical detector structure, coupled with the high quality of epitaxial layers, has resulted in a linearity and sensitivity of the detector that are significantly higher than those published previously for moderate dose rate testing.